Membangun Network Attached Storage (NAS) Untuk Integrasi Data Pada Stikes Al-Fatah Bengkulu - Debi Utomo; Sapri Sapri; Mesterjon Mesterjon (UNIVED Press, 2024)
One system that can be used as a network attached storage system or that can be used for storage is the Linux Ubuntu Server 20.04 operating system, which is an open source operating system, this operating system is very good for use as a server because it does not require high hardware specifications and It can also be obtained for free because it is open source. The network attached storage system using Linux Ubuntu server is very well applied to the Al-Fatah Stikes in Bengkulu City, this is because the Al-Fatah Stikes in Bengkulu City requires a shared storage system to make it easier for lecturers and students to collect, create and provide modules, with the existence of This system can help students and lecturers in lecture activities. The use of this system can help students in submitting assignments and searching for modules provided by lecturers. Each lecturer and student can only access the storage folder according to their respective account